Chromosomal effects of infections in malnourished and eutrophic children of Gran La Plata - Padula, Gisel (2008)
The aim of this study was to assess the induction of structural chromosomal aberrations in peripheral blood lymphocytes of malnourished and eutrophic children with bacterial infections. Thirty-six infants concurrent to the Hospital Interzonal de Agudos y Crónicos Dr. Alejandro Korn, La Plata, Argentina were included in this analysis; 11 infected and malnourished (IM), 7 infected and eutrophic (IE) and 18 non-infected and eutrophic (NE). Children aged 1-60 months. Anthropometric and clinic evaluation were performed to assess nutritional condition. We scored structural chromosome aberrations (SCA) in 100 metaphases per individual. Statistical analysis was performed by the Epi Dat 3.0 (OPS-OMS, 2003), through «Test de Diferencias entre dos proporciones muestrales» (p<0.05). Total SCE frequency was five times higher in IM children than that of IE ones (15,1% vs. 3,33% p<0,001) and two times greater in IE than in NE children (3,33% vs. 1,88% p<0.05). Results presented here showed an increase frequency of SCA not only in relation with malnutrition but also with the presence of bacterial infections. It is difficult to discern whether structural chromosome aberrations are due to malnutrition per se, bacterial or viral infections, antibiotics or all of these factors acting on malnourished tissues. In conclusion, mutagenic factors cause chromosomal changes more easily in an altered environment.